Fiber-Palladium Complex as Highly Active and Recyclable Catalyst for Heck Reaction in Air - Wu, Zhichuan; Wu, Qi; Chen, Meng; Tao, Tingxian (Asian Journal of Chemistry, 2013)
A new amidoxime fibers-palladium catalyst was synthesized by the "coordination-reduction" reaction between the amidoxime groups in fibers and Pd(II) ions. The morphology, structure and composition of the as-obtained complexes were characterized by X-ray diffraction and X-ray photoelectron spectroscopy. The results indicated that the Pd(II) ions were reduced to Pd(0) nanospheres in situ with the diameter of about 100 nm and there were coordination interactions between the Pd nanoparticles and the amidoxime fibers. The prepared catalyst demonstrated high activities for Heck coupling reaction of aryl iodine. During the reaction, the fibers serve as both the ligand and the support. In all cases, the coupling reactions proceeded efficiently without inert atmosphere. The catalyst can be easily recycled for at least eight times.